The effect of group size on individual behavior of bubble‐net feeding humpback whales in the southern Gulf of Maine - Natalie C. Mastick; David Wiley; David E. Cade; Colin Ware; Susan E. Parks; Ari S. Friedlaender (Marine Mammal Science, 2022)
In many species, group foraging is a strategy used to increase the efficiency of individuals to find and exploit patchy prey. Humpback whales ( Megaptera novaeangliae ) are one of the few baleen whale species reported to use coordinated foraging strategies. One of these behaviors, bubble‐net feeding, has been observed in several populations, though the behaviors of individuals within these groups are largely unknown. This study used multisensor kinematic tag data from 26 whales foraging in the Southern Gulf of Maine to analyze individual bubble‐net feeding behaviors. Linear mixed effects models were used to test if there were differences in individual whales' dive behaviors across group size. The results indicate that individuals performed consistent bubble‐net feeding behaviors regardless of the size of their foraging group, except when using one specific foraging behavior, the upward spiral. Overall complexity of foraging dives, based on the three‐dimensional movements of the dive, decreased with increasing group size when group members used upward spirals. This may indicate that in larger groups, participants in coordinated feeding events need to move less and expend less energy to corral prey. This study provides new insights into the effects of group size on individual behavior and group coordination in humpback whales.

Bottom side‐roll feeding by humpback whales ( Megaptera novaeangliae ) in the southern Gulf of Maine, U.S.A - Colin Ware; David N. Wiley; Ari S. Friedlaender; Mason Weinrich; Elliott L. Hazen; Alessandro Bocconcelli; Susan E. Parks; Alison K. Stimpert; Mike A. Thompson; Kyler Abernathy (Marine Mammal Science, 2014)
Humpback whales (Megaptera novaeangliae) are known for the variety and complexity of their feeding behaviors. Here we report on the use of synchronous motion and acoustic recording tags ( DTAG s) to provide the first detailed kinematic descriptions of humpback whales using bottom side‐rolls ( BSR s) to feed along the seafloor. We recorded 3,505 events from 19 animals (individual range 8–722). By animal, mean BSR duration ranged from 14.1 s to 36.2 s.; mean body roll angle from 80º to 121º, and mean pitch from 7º to 38º. The median interval between sequential BSR s, by animal, ranged from 24.0 s to 63.6 s and animals tended to maintain a consistent BSR heading during long BSR series encompassing multiple dives. BSR s were most frequent between 2200 and 0400. We identify three classes of behavior: simple side‐roll, side‐roll inversion, and repetitive scooping. Results indicate that BSR feeding is a common technique in the study area and there is both coordination and noncoordination between animals. We argue that this behavior is not lunge feeding as normally characterized, because animals are moving slowly through the event. The behavior also leads to vulnerability to entanglement in bottom‐set fishing gear, a major mortality factor for the species.

Shallow and deep lunge feeding of humpback whales in fjords of the West Antarctic Peninsula - Colin Ware; Ari S. Friedlaender; Douglas P. Nowacek (Marine Mammal Science, 2011)
Humpback whales ( Megaptera novaeangliae ) belong to the class of marine mammals known as rorquals that feed through extraordinarily energetic lunges during which they engulf large volumes of water equal to as much as 70% of their body mass. To understand the kinematics of humpback lunge feeding, we attached high‐resolution digital recording tags incorporating accelerometers, magnetometers, pressure and sound recording to whales feeding on euphausiids in fjords of the West Antarctic Peninsula. Instances of near vertical lunges gave us the unique opportunity to use the signal from the accelerometer to obtain a fine scale record of the body accelerations involved in lunging. We found that lunges contain extreme accelerations reaching 2.5 m/s 2 in certain instances, which are then followed by decelerations. When animals are intensively feeding the inter‐lunge interval is similar for both deep and shallow lunges suggesting a biomechanical constraint on lunges. However, the number of lunges per dive varies from one for shallow feeding (